Gendered dimensions of migration in relation to climate change. (21st April 2021) - Lama, Phudoma; Hamza, Mo; Wester, Misse
ABSTRACT: It is widely accepted that climate change may be contributing to population movement and has gendered effects. The relationship between climate change as a direct cause of migration continues to give rise to debates concerning vulnerabilities, while at the same time gendered dimensions of vulnerabilities remain limited to binary approaches. There is limited cross-fertilization between disciplines that go beyond comparison between males and females but interrogate gender in association with climate change and migration. Here, we seek to develop an analytical lens to the nexus between gender, migration and climate change in producing, reproducing and sustaining at risk conditions and vulnerabilities. When gender and mobility are conceptualized as a process, and climate change as a risk modifier, the nexus between them can be better interrogated. Starting by using gender as an organizing principle that structures and stratifies relations entails viewing gender not as a category that distinguishes males and females but as a discursive process of social construction that (re)produces subjectivities and inequalities. Gender is a dynamic process that shapes and (re)produces vulnerabilities and consequently shapes mediation of climate impacts and migration and is also shaped by symbolic processes that go beyond households and communities.